Conceptualising spirituality and religion as psychological processes: validation of the factor structure of the BMMRS. Issue 3 (16th March 2021) - Johnstone, Brick; Bruininks, Patricia; Smith, Erin I.; Yoon, Dong Pil; Cohen, Daniel; Edman, Laird; Bankard, Joseph; Witvliet, Charlotte
ABSTRACT: This study validated previous principal component analyses of the Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS) that have been conducted with persons with diverse medical conditions and traumatic brain injuries from diverse cultures (India, US), ethnicities (African American, Caucasian, South Asian), and religions (Christian, Hindu, Muslim). Participants included 398 healthy undergraduate students who completed the BMMRS online. A principal components factor analysis identified a five factor solution accounting for 64.00% of the variance in scores, labelled as: (1) Positive Spiritual Experience; (2) Negative Spiritual Experience/Congregational Support; (3) Forgiveness; (4) Religious Practices; and (5) Positive Congregational Support. The current analysis is supportive of a conceptual framework in which the BMMRS spiritual and religious variables are best conceptualised in terms of positive/negative psychological processes including: (a) emotional connection with the divine (i.e., spirituality ); (b) behavioural rituals/beliefs (i.e., religiosity ); and (c) social support (i.e., congregationally based ). Implications for psychoneuroimmunological research are discussed.